Smart materials for smart healthcare– moving from sensors and actuators to self-sustained nanoenergy nanosystems - Faezeh Arab Hassani; Qiongfeng Shi; Feng Wen; Tianyiyi He; Ahmed Haroun; Yanqin Yang; Yuqin Feng; Chengkuo Lee (Smart Materials in Medicine, 2020)
Smart materials offer a significant role in on our lives covering various sensing and actuation applications in healthcare due to their responsivity to external stimuli such as stress, light, temperature, moisture or pH, and electric or magnetic fields. These materials are also suitable for harvesting biomechanical energies from human motions, environment or body heat, or shaping of biofuel powered devices. This will open up the horizon for nanoenergy nanosystems that can themselves act as self-powered sensors or be utilized as power sources for other integrated transducers. This paper, gives an insight to the state-of-the-art micro/nano-systems that are proposed for implantable and wearable diagnostic, therapeutic and treatment applications. The unique property of these systems apart from the flexibility or conformability of the transducers (i.e. sensors and actuators) and the uniqueness of their building materials, is their integration with various types of energy harvesters that makes the whole system self-sustained or battery-free. The incorporation of these self-sustained systems into information technology affecting smart healthcare in significant ways.